PERA, RBTE Ve DBYBHY 2007 Yönetmeligi Kullanılarak Mevcut Bina Deprem Performanslarının Belirlenmesi - Özçelik, Muhammet Uğur (Fen Bilimleri Enstitüsü, 2014)
Mevcut binaların sayısını göz önünde bulundurduğumuzda performans degerlendirmelerinin yapılmasının klasik yöntemlerle uzun zaman alacagını ve kısa sürede bitirmek için kalabalık bir ekip gerektirecegini görebiliriz. Bu tez çalısmasında, bu soruna çözüm getirebilmek için hazırlanan Hızlı Deprem Performansı Degerlendirme Metodu olan PERA, Kocaeli İli sınırları içerisinde bulunan 6 adet bina üzerinde uygulandı. Her binadan 48, toplam 288 performans sonucu elde edildi. Sonuçlar DBYBHY 2007 ve RBTEİE yönetmelikleri ile karsılastırıldı.

A destructive earthquake hit Kocaeli province of Turkey on August 17, 1999. The magnitude of the earthquake was 7.5 Mw according to Richter scale. As a result of the earthquake, many buildings were damaged and collapsed either fully or partially. In this study, six existing buildings, which were constructed before 1999 Kocaeli earthquake are investigated in detail. The buildings are representative of typical 3-4 storey reinforced concrete buildings and survived against earthquakes by experiencing damages in different extents. Then the performances of these buildings are predicted by the PERA method and predictions are compared with the conclusions of detailed seismic assessment analysis such as DBYBHY2007 and RBTEİY. The comparisons validated the accuracy of the PERA algorithm for the investigated type of reinforced concrete buildings.
Seismic Assesment Of Existing Buikdings Using Pera,rbte And Dbybhy 2007
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2014
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2014
Keywords: tahmin; pera; rbteie; deprem; performans; hızlı; deprem güvenliği; riskli bina; Assessment; PERA; performance; rapid; reinforced concrete; seismic; safety